2022
DOI: 10.3390/genes14010107
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Linkage Disequilibrium, Effective Population Size, and Genetic Parameters of Phenotypic Traits in Dabieshan Cattle

Abstract: Dabieshan cattle (DBSC) are a valuable genetic resource for indigenous cattle breeds in China. It is a small to medium-sized breed with slower growth, but with good meat quality and fat deposition. Genetic markers could be used for the estimation of population genetic structure and genetic parameters. In this work, we genotyped the DBSC breeding population (n = 235) with the GeneSeek Genomic Profiler (GGP) 100 k density genomic chip. Genotype data of 222 individuals and 81,579 SNPs were retained after quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The method of Santiago et al (2020) has now been applied to different species, particularly in the last year, including insects, such as honeybees (Sang et al, 2022); birds, such as Black Robin (von Seth et al, 2022); fishes, such as turbot, seabream and seabass (Saura et al, 2021), Baltic herring (Atmore et al, 2022), pikeperch (De Los Ríos-Pérez et al, 2022, coho salmon (Martinez et al, 2022), catfish (Coimbra et al, 2023) and sailfish (Ferrette et al, 2023); wild mammals, such as grey wolf (Pacheco et al, 2022), killer whales (Kardos et al, 2023), sika deer (Iijima et al, 2023), scimitar-horned oryx (Humble et al, 2023) and gorilla (Alvarez-Estape et al, 2023); humans (Bird et al, 2023); domestic species, such as pigs (Krupa et al, 2022), cattle (Jin et al, 2022;Magnier et al, 2022), sheep (Djokic et al, 2023;Drzaic et al, 2022), horse (Criscione et al, 2022) and chicken (Gao et al, 2023;Liu et al, 2023); plants, such as walnut (Ding et al, 2022); crustaceans, such as Daphnia (Wersebe & Weider, 2023) and fungi (Singh et al, 2021). As suggested by Santiago et al (2020), the method is generally reliable for about 200 generations in the past, although…”
Section: Discussionmentioning
confidence: 99%
“…The method of Santiago et al (2020) has now been applied to different species, particularly in the last year, including insects, such as honeybees (Sang et al, 2022); birds, such as Black Robin (von Seth et al, 2022); fishes, such as turbot, seabream and seabass (Saura et al, 2021), Baltic herring (Atmore et al, 2022), pikeperch (De Los Ríos-Pérez et al, 2022, coho salmon (Martinez et al, 2022), catfish (Coimbra et al, 2023) and sailfish (Ferrette et al, 2023); wild mammals, such as grey wolf (Pacheco et al, 2022), killer whales (Kardos et al, 2023), sika deer (Iijima et al, 2023), scimitar-horned oryx (Humble et al, 2023) and gorilla (Alvarez-Estape et al, 2023); humans (Bird et al, 2023); domestic species, such as pigs (Krupa et al, 2022), cattle (Jin et al, 2022;Magnier et al, 2022), sheep (Djokic et al, 2023;Drzaic et al, 2022), horse (Criscione et al, 2022) and chicken (Gao et al, 2023;Liu et al, 2023); plants, such as walnut (Ding et al, 2022); crustaceans, such as Daphnia (Wersebe & Weider, 2023) and fungi (Singh et al, 2021). As suggested by Santiago et al (2020), the method is generally reliable for about 200 generations in the past, although…”
Section: Discussionmentioning
confidence: 99%
“…This approach on which SNeP relies for estimation of the historical N e is limited to the assumption of linear or steady population. Under this recently developed GONE software has been demonstrated with the ability to discern significant shifts in the historical N e [38][39][40][41][42]. A simulation study concluded that the N e derived using GONE reflects genuine demographic changes across generations and is not significantly impacted by selection or the heterogeneity in recombination rate across the genome [39].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, it is challenging to forecast with accuracy how drift will affect LD cumulatively over generations, especially when the recombination rate is low [14]. The GONE software has also been reported to work well with a small sample size [38]. When measuring the effective population sizes in turbot, seabream, European seabass, and common carp species of fish using GONE [40] discovered a similar pattern of drastic reduction of N e between the five to nine generations, and these declines might be related to the mixing, founder effect, and artificial selection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these results were similar to those estimated for indigenous cattle breeds from India (Strucken et al, 2021; N e = 13, 30 and 43), Bangladesh (Bhuiyan et al, 2021; N e = 26.02-108.29 until five generations ago), Korea (Sudrajad et al, 2016; N e = 53-60 11 generations ago), China and Japan ; N e = 27, 34 and 14 for South and North Chinese cattle, and Black Japanese breed, respectively) and South Africa (Dlamini et al, 2022; N e = 56-99 for five generations ago). Other native breeds such as Dabieshan Chinese cattle (Jin et al, 2022; N e = 86 for one generation ago) and Indian native cattle (Strucken et al, 2021; N e = 399 for one generation ago) exhibited higher values. The significant decrease of N e in recent generations in Creole cattle populations agrees with the high contribution of large segments of F ROH to the inbreeding values.…”
Section: Sc Usmentioning
confidence: 98%